Development of workability based approach for assessment of production temperatures of warm mix asphalt mixtures - Sukhija M.; Wagh V.P.; Saboo N. (My University, 2025)
Warm Mix Asphalt (WMA) is a sustainable technology that allows asphalt mixtures to be produced and compacted at lower temperatures in comparison to hot mix asphalt (HMA). Several concerns have been raised regarding the determination of mixing and compaction temperatures (also termed as production temperatures) for WMA mixtures. An attempt has been made through this study to comprehensively understand and explore the procedures for appropriate measurement of production temperatures of WMA mixtures. One base asphalt binder and five different warm mix additives (with varying dosages) were used in this direction. Rotational Viscometer (RV) and Dynamic Shear Rheometer (DSR) were employed to analyse the unmodified and warm mix modified asphalt binders. A workability prototype was fabricated, and a workability-based approach was proposed to systematically assess the production temperatures. Additionally, coating ability and compactability tests were carried out to validate the obtained mixing and compaction temperatures, respectively. It was found that production temperatures determined by testing asphalt binders through RV and DSR do not yield appropriate results for warm mix modified asphalt binders. Workability analysis showed that WMA mixtures, regardless of dosage and type, exhibit improved workability in comparison to the conventional HMA mixture, at all the test temperatures. Taking HMA mixture as a reference, the maximum reduction in mixing and compaction temperatures with the inclusion of WMA technologies was found to be 22 °C and 37 °C, respectively. In addition, WMA mixtures produced and compacted at reduced temperatures exhibited similar/better coating and consistent density in comparison to the conventional HMA mixture. It is concluded that the proposed workability approach for the evaluation of production temperatures of WMA mixtures is feasible and can be adopted. The output of the present study also appreciates the use of WMA for sustainable pavement construction. © 2021 Elsevier Ltd